PROBLEMATIKA PENEGAKAN HUKUM TERHADAP PENYEBARAN HOAKS POLITIK DI MEDIA SOSIAL - Abdullah Zahid (Journal of Law and Justice, 2025)
The problem of law enforcement against the spread of political hoaxes on social media in Indonesia following the 2024 elections, with 1,593 hoax cases recorded in the first year of the Prabowo-Gibran administration, nearly half of which were politically motivated and targeted the government. The background of this research is based on the rise of politically motivated disinformation that utilizes digital platform algorithms to produce negative campaigns, hate speech, and polarization, thus threatening social stability and the quality of democracy. The research aims to analyze the dominant forms of political hoaxes on social media and uncover the problems of law enforcement, including the multiple interpretations of the flexible articles of the Electronic Information and Transactions (ITE) Law, obstacles to digital evidence, limited capacity of officials, and weak inter-institutional coordination. The research uses a descriptive qualitative approach through a literature review of key regulations such as the ITE Law, the Criminal Code, the Election Law, Constitutional Court decisions, official reports from the Ministry of Communication and Information Technology (Kominfo) and academic studies related to political hoaxes and digital literacy. The research findings indicate that Indonesia's legal framework is relatively comprehensive, but implementation remains hampered by the anonymity of perpetrators, AI-generated hoax technology, disparities in cyber forensic capacity, and the risk of overcriminalization that blurs the line between freedom of expression and criminal acts. The study recommends strengthening more precise regulations, improving digital literacy, providing forensic training for officers, and close collaboration with digital platforms to ensure law enforcement against political hoaxes is more adaptive and effective in protecting the democratic public sphere.